Response to Video Experiments on Identification of Electrolyte and Non-Electrolyte Solutions with Easy, Cheap, and Environmentally Friendly Methods, Tools, and Materials Through Online Media - Yulia Widayanti; Sri Mulyanti; Ella Izzatin (Universitas Lampung, 2021)
During a pandemic like this, face-to-face learning is being transferred directly to online learning. Experiments with electrolyte and non-electrolyte solutions require student activity to achieve learning objectives, so an innovative and effective method and media are needed. The purpose of this study was to find out how the response of video viewers that had been distributed through youtube media, both in terms of quality, methods, materials, and chemical content discussed. The research method is by surveying the opinions (responses) of the audience who watched the video, then described qualitatively with graphic data from the response results as support. From the results of the video publication, it was obtained how the response was obtained statistically, and then the statistical data was analyzed based on the average response of each question. It was found that most of the audience agreed on the quality, easy application of the method, cheap materials, and the concept of electrolyte solution being discussed. It was concluded that the experimental media with video in this study could be a solution for teachers to keep teaching their students by practising independently at home with the video content in this study as a guide.